Life-history trait of the Mediterranean keystone species Patella rustica: growth and microbial bioerosion - PRUSINA, I.; PEHARDA, M.; EZGETA-BALIC, D.; PULJAS, S.; GLAMUZINA, B.; GOLUBIC, S. (Mediterranean Marine Science, 2015)
The age and shell growth patterns in populations of Patella rustica of the Adriatic Sea were determined by analyzing the inner growth lines visible in shell sections. Marginal increment analysis showed annual periodicity with annual growth line being deposited in May. The growth analysis of 120 individual shells showed that 90.8 % of collected individuals were less than 4 years of age and only two individuals (1.6 %) were older than 6 years. Population structure was described and the generalized von Bertalanffy growth parameters were calculated: asymptotic length (L∞) was 38.22 mm and the growth constant (K) was 0.30 year-1. Growth performance index value of P. rustica (Ø’) was 2.64 and is among the lowest ranges reported for limpet species. Patella rustica shells were degraded to different degrees by microbial bioerosion. Microboring organisms identified were pseudofilamentous and filamentous cyanobacteria Hormathonema paulocellulare, Hyella caespitosa, Mastigocoleus testarum and Leptolyngbya sp. The overall intensity of infestation was relatively low, but increased in severity with shell length. The damage was most often restricted to the oldest parts of the shell, i.e. apex of the shell, posing difficulties in determining the exact position of the first growth line. The present study is first to introduce the use of inner growth lines in Patella rustica shell sections as a reliable method for age determination and it provides the first insight into the growth patterns of this keystone species while taking the interference of microbial shell bioerosion in consideration.